1992
DOI: 10.1148/radiology.185.3.1438769
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration biopsy for cytopathologic analysis: utility of syringe handles, automated guns, and the nonsuction method.

Abstract: The performances of seven techniques and devices used with 22-gauge needles to obtain biopsy specimens for cytologic analysis were compared by means of single-blinded evaluation with an objective, previously published grading scheme. A total of 420 specimens were obtained from 10 fresh human cadavers (42 specimens per cadaver), including 30 hepatic, 20 renal, and 10 pancreatic specimens per technique or device. No statistical differences existed in the liver, kidney, or pancreas or in the combined data in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 0 publications
4
33
0
Order By: Relevance
“…The data in this study, however, confirm our previous blinded evaluation of the capillary vs aspiration technique [18]. As in our prior study, the capillary technique performed worse statistically than either the vacuum gun or the aspiration technique, especially with respect to the amount of cellular material obtained, and in the kidney, retention of appropriate architecture.…”
Section: Discussionsupporting
confidence: 84%
“…The data in this study, however, confirm our previous blinded evaluation of the capillary vs aspiration technique [18]. As in our prior study, the capillary technique performed worse statistically than either the vacuum gun or the aspiration technique, especially with respect to the amount of cellular material obtained, and in the kidney, retention of appropriate architecture.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have reported the superiority of aspiration needles, especially for lesions with low cellular density [14,15]. With regard to pancreatic masses specifically, Hopper et al [16] reported a clearly poorer performance of the capillary method sampling with regard to the amount of cellular material obtained, degree of cellular trauma, and overall diagnostic value. There were differences between the centres involved in this study with regard to the modality of re-evaluation in patients with non-diagnostic samples: excluding 42 patients who were lost to follow-up after non-diagnostic samples were obtained (26 in centre 1 and 16 in centre 2), most patients in centre 1 were referred to surgery (12/22) or EUS-FNA (5/22), while in centre 2 US-FNA was repeated in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that FNC may be better in the biopsy of lymph nodes, 7,8 whereas FNA may yield better specimens in pancreatic masses and sclerotic lesions. 9 However, these data are limited.…”
Section: Discussionmentioning
confidence: 99%